PJMHS 2022
DOI: 10.53350/pjmhs22161018
|View full text |Cite
|
Sign up to set email alerts
|

Obesity amongst Medical Students - A Cross-Sectional Comparative Study from Lahore, Pakistan, 2022

Abstract: Background: Doctors wellbeing not only affects them but also it has strong impact on their surroundings as they are considered as role models in community. Aim: To assess the magnitude and any overtime change of obesity among the medical students. Methods: This study was conducted at Ameer Ud Din Medical College Lahore from February to April 2022. Informed verbal consent was taken from 159 students selected through simple Random sampling that agreed and were not having any health ailments like ascites or ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Most students belonged to the age group of 21-23 years (n=204), and the majority were from the middle socioeconomic class (n=309, 93.4%), reflecting a population with generally healthy dietary habits. These results align with a study conducted among medical students in Lahore, where most students also had a normal BMI due to consuming a healthy diet (17). The study identified that 81 students (24.5%) were underweight, likely due to the study burden, while 36 students (10.9%) were overweight, and 10 students (3%) were obese.…”
Section: Discussionsupporting
confidence: 85%
“…Most students belonged to the age group of 21-23 years (n=204), and the majority were from the middle socioeconomic class (n=309, 93.4%), reflecting a population with generally healthy dietary habits. These results align with a study conducted among medical students in Lahore, where most students also had a normal BMI due to consuming a healthy diet (17). The study identified that 81 students (24.5%) were underweight, likely due to the study burden, while 36 students (10.9%) were overweight, and 10 students (3%) were obese.…”
Section: Discussionsupporting
confidence: 85%
“…Obesity has affected 400 million person all over the world. Pakistan is a developing country and also facing double burden as a result of under nutrition and over nutrition, According to WHO around 26% women while just 19% of the men are obese in Pakistan with urban population more affected comparative to rural (Khan, Khan, & Siddique, 2022). So, the current study is needed to be conducted to identify the knowledge and attitude to just highlight the need of future study on this seldom highlighted topic the knowledge and attitude towards obesity and bariatric surgery among nurses.…”
Section: Problem Statementmentioning
confidence: 99%